An epidemiological study of avian influenza A (H5) virus in nomadic ducks and their raising practices in northeastern Bangladesh, 2011‐2012. Issue 3 (2nd January 2017) - Sarkar, Shamim; Khan, Salah Uddin; Mikolon, Andrea; Rahman, Mohammad Ziaur; Abedin, Jaynal; Zeidner, Nord; Sturm‐Ramirez, Katherine; Luby, Stephen P.
Abstract : Background: In Bangladesh, nomadic duck flocks are groups of domestic ducks reared for egg production that are moved to access feeding sites beyond their owners' village boundaries and are housed overnight in portable enclosures in scavenging areas. The objectives of this study were to measure the prevalence of influenza A virus RNA and H5‐specific antibodies in nomadic ducks and to characterize nomadic duck raising practices in northeastern Bangladesh. Methods: We tested duck egg yolk specimens by competitive ELISA to detect antibodies against avian influenza A (H5) and environmental fecal samples by real‐time reverse‐transcription polymerase chain reaction (rRT‐PCR) to detect influenza A virus RNA and H5 subtype. Results: The median age of the ducks was 24 months (range: 8‐36 months) and the median flock size was 300 ducks (range: 105‐1100). Of 1860 egg yolk samples, 556 (30%, 95% confidence interval (CI): 28‐32) were positive for antibodies against H5 and 58 flocks (94%) had at least one egg with H5‐specific antibodies. Of 496 fecal samples, 121 (24%, 95% CI: 22‐29) had detectable influenza A RNA. Thirty‐three flocks (53%) had at least one fecal sample positive for influenza A RNA. Conclusions: Nomadic ducks in Bangladesh are commonly infected with avian influenza A (H5) virus and may serve as a bridging host for transmission of avian influenza A (H5) virus or other avian influenza A viruses subtypes between wild waterfowl, backyard poultry, and humans in Bangladesh.